Comparative safety evaluation of pentavalent (DTaP-IPV-Hib) and hexavalent (DTaP-IPV-Hib-HepB) vaccines in infants: a real-world analysis based on VAERS - Wei, Zhen; Li, Bai; Jia, Hong-Ling (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundCombination vaccines simplify immunization schedules and improve compliance, making them a global priority in pediatric immunization strategies. The DTaP-IPV-Hib pentavalent vaccine has been widely adopted, and with the incorporation of the hepatitis B vaccine (HepB), the DTaP-IPV-Hib-HepB hexavalent vaccine was developed. However, whether the addition of antigens in the hexavalent formulation is linked to differences in the reporting of adverse events following immunization (AEFIs) remains a matter of ongoing debate.ObjectiveThis study aims to compare the safety profiles and differences in AEFIs between the pentavalent vaccine and the hexavalent vaccine in infants aged 6 weeks to 2 years, based on real-world data from the U.S. Vaccine Adverse Event Reporting System (VAERS). The study also seeks to identify potential safety signals and evaluate correlates of death classification among reports.MethodsAEFIs reported to the VAERS from 2018 to 2024 were analyzed. Four disproportionality analysis methods—including Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-Item Gamma Poisson Shrinker (MGPS)—were used to identify potential safety signals. A multivariable logistic regression model was employed to examine factors associated with reports classified as death.ResultsA total of 4,980 AEFI reports were included (3,259 for the pentavalent vaccine and 1,720 for the hexavalent vaccine). Reports following hexavalent vaccination more frequently involved serious AEFIs—particularly hospitalization and life-threatening events—than reports following pentavalent vaccination, especially among infants aged 6 weeks to 4 months, in whom apnea and cyanosis were more frequently reported. Disproportionality analysis showed that reports for the hexavalent vaccine generated stronger disproportionality signals in multiple systems, including nervous system disorders (ROR = 1.95; IC025 = 0.70), vascular disorders (ROR = 2.89; IC025 = 1.17), cardiac disorders (ROR = 1.92; IC025 = 0.45), and respiratory disorders (ROR = 1.33; IC025 = 0.19). In the multivariable model, increasing age and female sex were associated with lower odds of reports being classified as death. Co-administration with other vaccines was associated with higher odds of death classification in the pentavalent subset, with no clear association observed in the hexavalent subset.ConclusionsWhile reports for both vaccines were generally consistent with known safety profiles, those following hexavalent vaccination showed stronger disproportionality signals in younger infants. These findings are hypothesis-generating and highlight the importance of targeted post-vaccination monitoring; they do not establish causality.